Penggunaan Aplikasi Kahoot Sebagai Alat Evaluasi Belajar dalam Meningkatkan Minat Belajar PAI Siswa Kelas 11 SMAN 10 Kota Bogor - Nila Mayang Sari; Sri Nurul Milla; Ikhwan Hamdani (Ikatan Dai Indonesia, 2025)
PAI plays an important role in shaping student character. The lack of technology utilization is one of the causes of low student interest in learning, especially in PAI. This study aims to determine the significance of differences in the increase in interest in PAI learning in classes using Kahoot application media and conventional methods, as well as comparing the effectiveness of both. This study used quantitative approach with quasi-experiment method and Nonequivalent Control Group Design. The sample consisted of two XI classes at SMAN 10 Bogor City: the experimental class used Kahoot and the control class used conventional methods. Data were collected through pre-test and post-test, then analyzed descriptively and inferentially using t-test and N-Gain Score. This study shows that the use of Kahoot application has a significant effect Sig (0.003) on increasing students' interest in learning in PAI subjects. The experimental class that used Kahoot experienced an increase in the average score of 12.1 points with an N-Gain of 66.6%, while the control class only increased by 4.9 points with an N-Gain of 25.1%. This study proves that the use of Kahoot application as a learning evaluation tool significantly increases students' interest in learning PAI subjects. The class that used Kahoot showed a higher increase in grades and motivation than the class with conventional methods. The statistical results reinforce this finding with the difference of.